Physical Attributes of Fashion Apparel that Influence the Purchase Intention of 20 to 24-Year-Old University Women in Lima - Arroyo Salazar, Jorge Hugo Omar (2023)
The objective of this research is to determine whether the physical attributes of fashion apparel significantly affect the purchase intention of 20 to 24-year-old university women in Lima, Peru. Based on the answer to this question, product development activities oriented at satisfying this consumer are more assured, because a producer can direct resources to key activities in order to obtain competitive products. For this reason, an applied study following a correlational approach was conducted, in which the statistical method was used according to the multiple regression test. Data collection was carried out using the survey technique in the study unit. The analysis of the responses leads to measuring the influence that certain factors have on purchase intention, ranking physical attributes on a scale of importance, and concluding that physical attributes significantly influence purchase intention.